Fetal MRI in the Identification of a Fetal Ventral Wall Defect Spectrum - Peter W. Coleman; Megan B. Marine; Jennifer N. Weida; Brian W. Gray; Deborah F. Billmire; Brandon P. Brown (Thieme Medical Publishers, Inc., 2018)
Abstract Objective To ascertain if useful criteria for prenatal diagnosis of fetal ventral body wall defects (VBWDs) exists by reviewing published literature on diagnosis of VBWD as compared with our own diagnostic experience. Study Design A comprehensive literature review of diagnostic criteria of fetal VBWD including pentalogy of Cantrell (POC), omphalocele, exstrophy, imperforate anus, spina bifida (OEIS), cloacal exstrophy, limb-body wall complex (LBWC), and body stalk anomaly was performed followed by a retrospective review of all fetal magnetic resonance imaging (MRI) examinations from our medical center over a 2-year period. Results Classically, OEIS is omphalocele, bladder exstrophy, imperforate anus, and spina bifida. POC is defects of the supraumbilical abdomen, sternum, diaphragm, pericardium, and heart. LBWC is two of the following: exencephaly or enencephaly with facial clefts, thoracoschisis or abdominoschisis, and limb defects. Twenty-four cases of VBWD on MRI over a 24-month period were identified with seven cases involving defects of additional organ systems. Six of these seven cases demonstrated findings from two or more of the traditional diagnoses POC, OEIS, and LBWC making diagnosis and counseling difficult. Conclusion There is a lack of consensus on useful diagnostic criteria within the published literature which is reflected in our own diagnostic experience and poses a challenge for accurate prenatal counseling.